ANALYSIS OF THE CORRELATION BETWEEN APPARENT POWER AND CURRENT LOADING ON VOLTAGE AND CURRENT IMBALANCE IN KM. SUMBER MANDIRI ELECTRIC GENERATOR - Demeianto, Bobby; Mahendra, Taufan; Siahaan, Juniawan Preston; Priharanto, Yuniar Endri (Politeknik Kelautan dan Perikanan Dumai, 2023)
Numerous studies have been conducted on voltage and current imbalance in three-phase electrical installations, but there has been no research specifically analyzing the correlation between voltage and current imbalances in the electric generators of fishing vessels. This study aims to investigate and analyze potential relationships among four key variables within this research context: apparent power, generator loading percentage, voltage imbalance, and current imbalance aboard KM. Sumber Mandiri.The research findings reveal the Pearson correlation coefficient value indicating the average generator loading percentage's correlation with the average current imbalance to be only 2.47%. Additionally, the average apparent power's Pearson correlation coefficient with the average current imbalance on the KM. Sumber Mandiri generator between November 17, 2022, and November 26, 2022, is calculated to be 0.29%. Moreover, the average generator loading percentage's Pearson correlation coefficient with the average voltage imbalance stands at 27.58%, while the average apparent power's Pearson correlation coefficient with the average voltage imbalance is at 40.91%. The fluctuations in current imbalance in relation to the variation in voltage imbalance on the KM. Sumber Mandiri generator show an impact of 14.03%, while the remaining 85.97% is attributed to other factors. The outcomes of this research are expected to provide valuable insights into the understanding of factors influencing voltage and current imbalance from a statistical perspective. Additionally, this study may assist in enhancing and designing more efficient and reliable electrical systems in three-phase installations aboard KM. Sumber Mandiri.